Commercial Shrimp Farming at Coastal Areas in Bangladesh and Its Effects on Livelihood and Environment: A Study on Paikgacha Upazila, Khulna (Dhaka University Journal of Science, 2018)
The study focuses on the changing livelihood pattern and the environment through shrimp farming in Bangladesh where the country is one of the largest producers of shrimp in the whole world. Shrimp production sector is contributing to the national economy of Bangladesh very fast other than any other sectors. This sector is the second top production sector of the century. This study was based on survey method; especially survey was done by questionnaire survey, where the primary data were collected from questionnaire survey. Although the environmental impact of shrimp cultivation is very adverse, the sector is becoming more popular because of huge profit. Therefore, the study found the change in pattern along with occupation, land use practice, sources of food, specially protein intake, transportation etc. Furthermore, the study found the adverse impact of intruding brackish water on surrounding environment and both on flora and fauna.Dhaka Univ. J. Sci. 66(2): 87-90, 2018 (July)